2009
DOI: 10.1099/mic.0.025270-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of signal peptide prediction algorithms for identification of mycobacterial signal peptides using sequence data from proteomic methods

Abstract: Secreted proteins play an important part in the pathogenicity of Mycobacterium tuberculosis, and are the primary source of vaccine and diagnostic candidates. A majority of these proteins are exported via the signal peptidase I-dependent pathway, and have a signal peptide that is cleaved off during the secretion process. Sequence similarities within signal peptides have spurred the development of several algorithms for predicting their presence as well as the respective cleavage sites. For proteins exported via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 41 publications
4
29
0
Order By: Relevance
“…A set of 53 experimentally verified, classically secreted mycobacterial proteins was obtained from Leversen and co-workers (Leversen et al, 2009). A set of non-classically secreted mycobacterial proteins, including proteins secreted by Tat or SecA2 systems, was assembled by performing a literature search.…”
Section: Methodsmentioning
confidence: 99%
“…A set of 53 experimentally verified, classically secreted mycobacterial proteins was obtained from Leversen and co-workers (Leversen et al, 2009). A set of non-classically secreted mycobacterial proteins, including proteins secreted by Tat or SecA2 systems, was assembled by performing a literature search.…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have evaluated the performance of signal peptide prediction programs using experimentally verified signal peptide data from different organisms (61)(62)(63). To the best of our knowledge, the suitability of the commonly used prediction programs to predict secretory proteins and signal peptide cleavage sites in S. aureus has not been reported.…”
Section: Post-translational Modifications Of Secreted Proteins-mentioning
confidence: 99%
“…For example, the set of cleaved proteins of Mycobacterium tuberculosis was extended to 57 through the use of high-accuracy MS instrumentation and advanced database design [7,8]. This data set was later used to validate signal peptide prediction algorithms [9], and the study found the Hidden Markov model (HMM) of SignalP v3.0 to be the most accurate tool. The HMM correctly predicted the presence or absence of a signal peptide, and the correct cleavage site in a high proportion of the proteins.…”
Section: Introductionmentioning
confidence: 99%